STRATEGIC MANAGEMENT IN INCREASING CUSTOMER SATISFACTION THROUGH SERVICE QUALITY AT GACOAN NOODLE CUSTOMERS IN SURABAYA - Aini, Melinda Nur; Rahman, Abdur (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
Customer satisfaction of a company is very dependent on the quality of service owned by the company. The quality of service that customers expect is not just providing the best service but fulfilling customer needs. The purpose of this study was to determine the strategy of increasing customer satisfaction at the Gacoan Noodle shop in Surabaya. This research uses qualitative research methods by collecting data from various sources, including manuscripts, journals, books, and other relevant and literature interviews with the Gacoan Noodle Company. In addition, in this article we introduce some reference results based on previous researchers regarding strategies to increase customer satisfaction through service quality. The results of this study indicate that the strategic management of Gacoan Surabaya noodle shop in fulfilling customer satisfaction with its service quality, has been running well and has been improved and can be used as a guideline for implementing strategic management practices to meet customer needs. This is because service quality is one of the actions to satisfy customers by providing service to customers as well as possible.